The Last ever after [Posledný a naveky anglicky] / [book 3] - Chainani, Soman (The School for Good and Evil, 2015)
With the girls apart, Evil has taken over and the villains of the past have come back to turn the world of Good and Evil upside down. With the forces of Good in deathly peril, Agatha and Sophie must work together to restore balance. Will they find their way to being friends again?